2013
DOI: 10.1002/jclp.21966
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Cascades and Self‐Injury: Investigating Instability of Rumination and Negative Emotion

Abstract: Consistent with the ECM, the interaction between rumination instability and negative affect instability during monitoring significantly predicted NSSI, with the strongest effects occurring for sadness and rumination about past. These findings may enhance conceptualization and treatment of patients with NSSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 41 publications
7
149
0
2
Order By: Relevance
“…Indeed, preoccupied states of mind regarding early caregiving experiences imply continued rumination on these experiences and associated emotional distress. Prior evidence indicates both rumination (e.g., Selby, Franklin, Carson-Wong, & Rizvi, 2013; Voon, Hasking, & Martin, 2014) and dysregulated emotional processes (e.g., Glenn, Blumenthal, Klonsky, & Hajcak, 2011; Plener, Bubalo, Fladung, Ludolph, & Lulé, 2012) are key risk factors for NSSI, and provide one explanation as to why preoccupied states of mind are a mechanism by which childhood abuse or neglect is related to NSSI. Specifically, the heightened emotionality and ruminative tendencies of individuals with preoccupied states of mind regarding early experiences may serve as triggers for NSSI behavior, particularly in combination with deficits in the capacity for regulating emotional distress known to be associated with childhood abuse or neglect (e.g., Kim & Cicchetti, 2009; Maughan & Cicchetti, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, preoccupied states of mind regarding early caregiving experiences imply continued rumination on these experiences and associated emotional distress. Prior evidence indicates both rumination (e.g., Selby, Franklin, Carson-Wong, & Rizvi, 2013; Voon, Hasking, & Martin, 2014) and dysregulated emotional processes (e.g., Glenn, Blumenthal, Klonsky, & Hajcak, 2011; Plener, Bubalo, Fladung, Ludolph, & Lulé, 2012) are key risk factors for NSSI, and provide one explanation as to why preoccupied states of mind are a mechanism by which childhood abuse or neglect is related to NSSI. Specifically, the heightened emotionality and ruminative tendencies of individuals with preoccupied states of mind regarding early experiences may serve as triggers for NSSI behavior, particularly in combination with deficits in the capacity for regulating emotional distress known to be associated with childhood abuse or neglect (e.g., Kim & Cicchetti, 2009; Maughan & Cicchetti, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, NSSI has been linked to deficits in emotion regulation (Adrian, Zeman, Erdley, Lisa, & Sim, 2011; Martin, Bureau, Yurkowski, Lafontaine, & Cloutier, 2016), high negative emotionality (Glenn, Blumenthal, Klonsky, & Hajcak, 2011; Najmi, Wegner, & Nock, 2007; Nock & Mendes, 2008; Plener, Bubalo, Fladung, Ludolph, & Lulé, 2012), and ruminative tendencies (Selby, Franklin, Carson-Wong, & Rizvi, 2013; Voon, Hasking, & Martin, 2014; Zaki, Coifman, Rafaeli, Berenson, & Downey, 2013). Thus, research and theory support the hypothesis that preoccupied (but not dismissing) attachment states of mind regarding both childhood caregivers and adult romantic partners should be associated with NSSI.…”
Section: Preoccupied States Of Mind Regarding Attachment and Nssimentioning
confidence: 99%
“…Researchers should also utilize ecological momentary assessment (EMA) techniques to better understand the relationship between impulsivity and NSSI. EMA studies have demonstrated equivocal evidence of impulsive NSSI behavior (see Armey et al 2011;Selby et al 2013). EMA studies could be utilized to assess the time between the urge to self-injure and the NSSI behavior in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…Included studies were also conducted across a range of nonclinical and clinical settings. With regard to nonclinical settings, 13 studies utilized entirely community-based participants, 4 used incarcerated (e.g., jail, community corrections) individuals, and 7 were conducted in school settings (e.g., high school, college, graduate school); one study used a combination of community-based and undergraduate participants (Selby, Franklin, Carson-Wong, & Rizvi, 2013). With regard to clinical settings, 21 studies were conducted in inpatient settings and 10 in outpatient settings.…”
Section: Description Of Included Studiesmentioning
confidence: 99%